2010
DOI: 10.14295/bds.1999.v2i2.46
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da prevalência de disfunção craniomandibular segundo o índice de Helkimo tendo como variáveis: sexo, faixa etária e indivíduos tratados ou não ortodonticamente

Abstract: Cem indivíduos com idades entre 18 e 25 anos, estudantes de Odontologia, não pacientes, foram entrevistados e examinados clinicamente com o objetivo de se avaliar a prevalência e o grau de severidade de Disfunção Craniomandibular. Para tal, foram utilizados índices que constam de avaliações subdivididas em três classificações diferentes: índice anamnético, disfunção clínica e oclusal, levando-se em consideração variáveis como sexo, faixa etária e o fato de terem sido submetidos, ou não, a tratamento ortodôntic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
0
2
0
6
Order By: Relevance
“…9,11,12,14,23 All studies cited in this literature review reported that orthodontic treatment did not provide risk to the development of signs and symptoms of TMD, regardless of the technique used for treatment, whether or not the extraction of premolars was performed, and the type of malocclusion previously presented by the patient. 8,9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]27 Some long-term studies concluded that the orthodontic treatment would not be preventive or a treatment modality for TMD. 9,15,27 Henrikson and Nilmer 24 suggested that due to the fluctuating character of the signs and symptoms of TMD, and as orthodontic treatment is not effective in treating TMD, a conservative and reversible approach should be adopted in the treatment of TMD, which agrees with the guidelines of the American Academy of Orofacial Pain.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,12,14,23 All studies cited in this literature review reported that orthodontic treatment did not provide risk to the development of signs and symptoms of TMD, regardless of the technique used for treatment, whether or not the extraction of premolars was performed, and the type of malocclusion previously presented by the patient. 8,9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]27 Some long-term studies concluded that the orthodontic treatment would not be preventive or a treatment modality for TMD. 9,15,27 Henrikson and Nilmer 24 suggested that due to the fluctuating character of the signs and symptoms of TMD, and as orthodontic treatment is not effective in treating TMD, a conservative and reversible approach should be adopted in the treatment of TMD, which agrees with the guidelines of the American Academy of Orofacial Pain.…”
Section: Discussionmentioning
confidence: 99%
“…Cerca de 70% de todosos casos dos participantes desse estudo foram classificados como severos nos dois índices anamnésicos. Os dados analisados revelaram predominância de indivíduos do gênero feminino (93%) portando DTM na faixa etária entre 21 e 40 anos, o que está de acordo com a maioria dos trabalhos sobre o assunto (BOVE et al, 2005;PEREIRA et al, 2005;MACFARLANE et al, 2002;LIMA et al, 1999;DONEGÁ et al, 1997).…”
Section: Discussionunclassified
“…O desconforto oclusal apresentou-se severo em somente 18% dos componentes desse estudo. Estudos como os de Lima et al (1999), que avaliaram clinicamente a oclusão, obseraram que o índice de disfunção clínica moderado e severo não foi necessariamente desencadeado por uma má oclusão severa já que dos 12% indivíduos com oclusão severa não apresentaram sintomatologia severa.…”
Section: Re Vis T a Cade R No S U Nif O A Revis Ta Cie N Tí F Ic A D unclassified
“…Em relação à idade, pode ocorrer em qualquer faixa etária, mas é mais comum dos 21 aos 40 anos (Bianchini, 2000;Berretin-Felix et al, 2005, Sarlani;Greenspan, 2005;Biasotto-Gonzales, 2005 (Lima et al, 1999).…”
Section: Distúrbios Temporomandibularesunclassified